Empowering Parents' Choice of Schools: The Rhetoric and Reality of How Hong Kong Kindergarten Parents Choose Schools Under the Voucher Scheme - Kit-ho Fung; Chi-chung Lam (Arizona State University, 2011)
School choice gives parents greater power over their childrenâs education. But ever since the Pre-primary Education Voucher Scheme (PEVS) was introduced in Hong Kong in 2007, school choice has become a hotly debated topic. The scheme was introduced to empower kindergarten parents in choosing a school for their children by offering them direct fee subsidies that, in return, could propel education quality forward. Parents in the private kindergarten sector, however, have long enjoyed the privilege of choice, and they have been preoccupied with an intense interest in their children's academic upbringing, even if it means compromising the holistic development of their children. This runs counter to the principles of a quality education. Therefore, the urge to further promote parental kindergarten choice will likely allow parental academic interests to continue to prevail and hence invalidate the PEVS' promise to improve education quality. The result is a unique dilemma between school choice for parents and the promise of education quality within Hong Kong's unique private kindergarten sector.